Occurrence, Transmission and Remedial Aspects of Drechslera oryzae in Paddy (Oryza sativa L.) - C.D. KRISHNAMURTHY; S.LOKESH; H.S.SHETTY (Seed Research, 2026)
Among the paddy seed samples, Jaya variety showed high incidence of Drechslera oryzae. The severity of the pathogen expressed an array of seedling symptoms like yellowing, brown necrosis, spots, streaks and decaying. The rate of symptom expression was more in case of artificially coated samples than its corresponding control. Hot water treatment at 60°C remained most effective in suppressing the colonization of D. oryzae. However, 55°C was found to enhance the seed germination and seedling growth. In case of three fungicides, Hadron at 0.1% level reduced the incidence of target pathogen and enhanced the seed germination percentage and seedling growth over control. Trichoderma pseudokoningii was most useful not only in controlling the incidence of D. oryzae but also increased the percentage of seed germination and seedling growth over control and other antagonists. Aqueous leaf extracts of Thuja orientalis proved a better treatment for the minimization of D. oyzae which in turn enhanced the seed germination and seedling growth compared to its control.